Memaknai Kembali Spiritualitas Islam Dalam Peradaban Kontemporer - Baedhowi Baedhowi (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2004)
This article tries to describe the reinterpretation of the Islamic spirituality in contemporary era. The writer explores the short history in sufism as a source of Islamic spirituality. He also wants to explore how to interprete the sufism as a product of history. From its history, we can know the development of sufisme period to period. In other hand, we can also reinterprete the meaning of Islamic spirituality in the contemporary civilization or modernism point of view. For example, we can know how to reinterprete the concept o f “wahdat al-wujud” and “wahdat al-adyan” as a main part of spirituality in Islam. This reinterpretation is expected to contribute the moral ethic or spirituality in contemporary era.